Training Model of Pencak Silat Gymnastics Skills for Children aged 13-16 Years - Resty Nausanty; Eva Julianti P; Widiastuti, Widiastuti; Oman U. Subandi; Fahmy Fachrezzy (UNIB Press, 2024)
The background of this research is the lack of children's activity in carrying out basic pencak silat techniques. The aim of this research is to produce products and determine the effectiveness of basic Pencak Silat technique training through the Pencak Silat Gymnastics skills training model for children aged 13-16 years. This research uses the ADDIE research and development model research method. This research was conducted at the Sasana Terate Jaya Club Indonesian Pencak Silat Padepokan with research subjects being children aged 13-16 years, in March - June 2024. The results of this research using a paired sample T test showed that the tcount was 22.708 with a significance value (Sig. 2-tailed) is 0.000 < 0.05. which means there is a significant difference between before and after being given the pencak silat training model treatment. So it can be concluded that the pencak silat gymnastics training model for children aged 13-16 years is effective and can be used in training to improve basic pencak silat movement skills.